Fast positioning for X‐ray scanning microscopy by a combined motion of sample and beam‐defining optics. (25th January 2019) - Odstrcil, Michal; Lebugle, Maxime; Lachat, Thierry; Raabe, Jörg; Holler, Mirko
Abstract : A novel approach for fast ptychography scans over an extended field of view by means of simultaneous Fresnel zone plate and sample motion is presented. Abstract : Scanning X‐ray microscopy such as X‐ray ptychography requires accurate and fast positioning of samples in the X‐ray beam. Sample stages often have a high mobile mass as they may carry additional mechanics or mirrors for position measurements. The high mobile mass of a piezo stage can introduce vibrations in the setup that will lead to imaging quality deterioration. Sample stages also require a large travel range which results in a slow positioning step response and thus high positioning overhead. Moving lightweight X‐ray optics, such as focusing Fresnel zone plates, instead of the sample can improve the situation but it may lead to undesired variations in the illumination probe which may result in reconstruction artifacts. This paper presents a combined approach in which a slow sample stage mechanism covers the long distance range for a large field of view, and a light‐weight optics scanner with a small travel range creates a superimposed motion to achieve a fast step response. The step response in the ptychographic tomography instrument used was thereby improved by an order of magnitude, allowing for efficient measurement without loss of imaging quality.